Briarenols O and P: Novel briaranes from a cultured octocoral Briareum excavatum (Briareidae). (February 2021) - Chi, Wei-Chiung; Kuo, Liang-Mou; Yang, San-Nan; Lee, Yi-Ting; Wen, Zhi-Hong; Tsui, Kuan-Hao; Hwang, Tsong-Long; Zhang, Yi-Lin; Sung, Ping-Jyun
Graphical abstract: Highlights: Novel briaranes, briarenols O (1 ) and P (2 ), were obtained from a cultured octocoral B. excavatum . Briarane 1 was found to enhance the protein expression of iNOS. Cultivated B. excavatum is a rich source of briarane-type diterpenoids. Abstract: Two new 3, 8-cyclized cembranoids, briarenols O (1 ) and P (2 ), featuring with briarane carbon skeleton have been isolated from a cultured octocoral Briareum excavatum . The structures of 1 and 2 were established by spectroscopic methods and 1 was found to be a rare 2-ketobriarane. Briarane 1 enhanced the generation of inducible nitric oxide synthase (iNOS) from RAW 264.7 stimulated by lipopolysaccharides (LPS).